Communication—Highly Sensitive Glassy Carbon Electrode Altered by Nanoporous Gold for the Electrochemical Detection of Nitrite. Issue 8 (29th April 2020) - Zhang, An; Yang, Zhipeng; Chen, Yuanyuan; Schützendübe, Peter; Huang, Yuan; Liu, Yongchang; Wang, Zumin
Abstract : Nanoporous gold (NPG) is a type of functional material that has been extensively investigated. Herein, a solid-phase reaction method was used to develop in situ NPG thin-film comprising Au nanobranch structures. The proposed method was found to be simple, fast and without complicated procedures. Electrochemical detection of nitrite was performed through cyclic voltammetry and linear sweep voltammetry. Test results demonstrated that the improved catalytic behaviour of the NPG for nitrite electro-oxidation reaction is highly dependent on its unique morphology. These findings are expected to provide an effective and rational pathway for the design and optimization of nitrite electrochemical sensors.